Pengaruh Penambahan FAME Terhadap Parameter CCR (Condradson Carbon Residu) Dan Sulfur Content Pada Produk Biosolar - Komis komis; Dwi Fitri Yani; Aji Nugraha (Jurnal Kimia Fullerene, 2023)
The increasing number of vehicles in Indonesia causes the need for energy to increase. This situation has an impact on the decreasing availability of fuel oil. Currently, the Government of Indonesia has stipulated in the Regulation of the Minister of Energy and Mineral Resources No. 12 of 2015 the use of FAME mixed fuel by 30% in diesel products (B30). But it does not rule out the possibility that Indonesia will increase the content of FAME. So this study aims to determine the effect of adding FAME to Biosolar products on CCR and Sulfur Content parameters. The methods used are CCR (condradson carbon residue) analysis using ASTM D-189 and Sulfur Content Analysis using ASTM D-4294. The results showed that the higher the FAME, the higher the residual carbon value and the results for B0, B30, B35, and B40 were 0.0257; 0.039; 0.063; 0.0787%. While the value of sulfur content is decreasing where the more FAME is added to biodiesel products, the sulfur content in these products decreases in B0, B30, B35, and B40, namely 0.181; 0.114; 0.104; 0.096%.